2020
DOI: 10.2147/dmso.s234992
|View full text |Cite
|
Sign up to set email alerts
|

<p>The Exercise Training Modulatory Effects on the Obesity-Induced Immunometabolic Dysfunctions</p>

Abstract: Reduced physical activity rate in people's lifestyle is a global concern associated with the prevalence of health disorders such as obesity and metabolic disturbance. Ample evidence has indicated a critical role of the immune system in the aggravation of obesity. The type, duration, and production of adipose tissue-released mediators may change subsequent inactive lifestyle-induced obesity, leading to the chronic systematic inflammation and monocyte/macrophage (MON/MФ) phenotype polarization. Preliminary adipo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 214 publications
(355 reference statements)
0
10
0
6
Order By: Relevance
“…MDD, dyslipidemia, and insulin resistance are said to share immunoinflammatory alterations (35). Exercise training is potent to interrupt the obesity-induced inflammatory mechanisms (36) and can be utilized to improve cholesterol levels (37). As a result, physical activity might prevent depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…MDD, dyslipidemia, and insulin resistance are said to share immunoinflammatory alterations (35). Exercise training is potent to interrupt the obesity-induced inflammatory mechanisms (36) and can be utilized to improve cholesterol levels (37). As a result, physical activity might prevent depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies have revealed that high-fat diets increase TLR4 gene levels compared to normal chow [20]. Although the acute protocols have not significantly changed TLR4 mRNA levels, the increase in the duration of training protocols appears to shift these results toward a reduction of TLR4 levels [33]. According to human studies, both acute, though not all, types of exercise (HIIT) [23] and long-term interventions downregulate TLR4 in the obese, healthy, and type 2 diabetes subjects [24,34,35]; this corresponds with the findings here.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous authors agree in the effects of physical exercise on the AT [ 18 , 19 , 20 , 21 ], such as changes in the AT phenotype that lead to a significant decrease of M1 macrophages and an increase of M2 macrophages, as well as the secretion of more anti-inflammatory cytokines, such as IL-6 and TNF-α [ 22 ]. Other researchers have studied the possible changes in the signaling pathways after implementing exercise programs, reporting a decrease of postprandial lipemia, a reduction in NF-kB signaling, and an increase in AMPK signaling (showing anti-inflammatory properties) [ 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%